(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
Information security appears not only as one of the forms of security, but also as a cross-section of all forms of security in which information technologies occupy an important place. The concept, content and substance of information security in the doctrines of the United States and the Russian Federation are defined in different ways. The different levels of socio-economic development and different levels of development and application of modern information technologies, lead to seemingly diametrically opposed stops in understanding the term information security. The paper elaborates in information security in the Russian Federation it is defined by the attitude of the general science of safety.